Exploring Decomposer Microorganisms in Making Goat Manure Fertilizer - Wayan Wariata; Tia Febrianti; Anwar Rosyidi; Hasma Hasma (Jurnal Biologi Tropis, 2026)
This study aimed to investigate the presence of decomposer microorganisms in the production of organic fertilizer derived from goat manure fermented using Local Microorganisms (MOL). The research was conducted at the Teaching Farm Lingsar and the Biotechnology and Animal Products Laboratory, Faculty of Animal Science, University of Mataram, from January to February 2026. The study employed a fermentation process in which goat manure was fermented with MOL for 30 days, followed by microbial isolation and enumeration using the Total Plate Count (TPC) method. The observed parameters included the population of lactic acid bacteria (LAB) and the population of molds/fungi as indicators of decomposer microorganisms. The data were analyzed using a paired sample t-test. The results showed that the average bacterial population increased from 5.67 log CFU/g in the control treatment (P0) to 6.33 log CFU/g in the fermentation treatment (P1), while the average mold population increased from 6.00 colonies/g to 10.67 log CFU/g. However, statistical analysis indicated that these increases were not significantly different (P > 0.05). Nevertheless, the presence of microorganisms in both treatments suggested that the decomposition process continued to occur and had the potential to support the formation of more stable organic fertilizer.  Therefore, the fermentation of goat manure using MOL did not have a significant effect on the population of decomposer microorganisms, although it still contributed to the decomposition of organic matter.